Preparation method and application of self-dispersing nitrogen copper modified carbon quantum dot water-borne epoxy resin anticorrosive paint

By using carbon quantum dots modified by self-dispersed nitrogen copper in aqueous epoxy resin, the problems of poor conductivity and poor dispersion of the aqueous epoxy resin are solved, and its corrosion and impact resistance are significantly improved to form a stable protective layer.

CN119463622APending Publication Date: 2025-02-18TONGHUA POWER SUPPLY COMPANY STATE GRID JILIN ELECTRIC POWER +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411131408.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-18
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing water-based epoxy resin anti-corrosion coatings have poor conductivity and poor dispersion, which leads to poor performance in corrosion and wear resistance, and are especially not suitable for places with high anti-corrosion and wear resistance requirements.

Method used

Carbon quantum dots modified by self-dispersed nitrogen copper are modified in aqueous epoxy resin, and efficiently dispersed nitrogen copper modified carbon quantum dots water-based epoxy resin anticorrosion coatings are prepared through ultrasonic dispersion, hydrothermal reaction and dialysis.

Benefits of technology

It significantly improves the corrosion resistance and impact resistance of the coating, enhances the conductivity and dispersion of the aqueous epoxy resin, forms a stable protective layer, and effectively prevents the interaction between the steel plate and corrosive elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463622A_ABST
    Figure CN119463622A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of metal anti-corrosion coatings, and particularly relates to a preparation method and application of a self-dispersing nitrogen copper modified carbon quantum dot water-borne epoxy resin anti-corrosion coating. The method is mainly used for steel sheet surface corrosion resistance. The preparation method comprises the following steps: preparing nitrogen-copper modified carbon quantum dots: ultrasonically and uniformly dispersing citric acid, disodium ethylene diamine tetraacetate and copper nitrate in deionized water and absolute ethyl alcohol, pouring the mixed solution into a polytetrafluoroethylene reaction kettle, putting the polytetrafluoroethylene reaction kettle into a drying oven at 180 DEG C, reacting for 10 hours, and heating in a water bath to prepare nitrogen-copper modified carbon quantum dot filler; the prepared filler, the water-borne epoxy resin and the curing agent are uniformly stirred to prepare the anticorrosive coating, the surface of the Q235 steel is coated with the prepared coating, and the anticorrosive coating is good in dispersity, good in anticorrosive effect and low in implementation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal anti-corrosion coating preparation, and particularly relates to a preparation method and application of a self-dispersed nitrogen copper modified carbon quantum dot waterborne epoxy resin anti-corrosion coating, which is mainly used for anti-corrosion of steel sheet surface. Background Art

[0002] Metals are used in industrial production and life as important engineering materials. The hazards and losses of metal corrosion have become the focus of attention. Coating anti-corrosion for metal corrosion is currently the most frequently used and most cost-effective metal anti-corrosion method. According to the different film-forming mechanisms, anti-corrosion coatings can be divided into acrylic, polyurethane, inorganic zinc-rich and epoxy anti-corrosion coatings. Water-based epoxy resins are widely used in the field of anti-corrosion due to their strong adaptability, environmental friendliness and low cost. However, single water-based epoxy resins have low hardness, poor durability and poor anti-corrosion effect, and are not suitable for places with high requirements for anti-corrosion and wear resistance.

[0003] Carbon quantum dots are a type of zero-dimensional carbon nanomaterial that has good water solubility, chemical stability, and non-toxic properties. They are usually used as corrosion inhibitors to inhibit metal corrosion. Ordinary carbon quantum dots have low strength and hardness and are easily oxidized. By doping with ions, the structure of carbon quantum dots can be changed, effectively improving their antioxidant ability; they have good compatibility in water-based epoxy resin coatings and can effectively eliminate defects generated during solvent evaporation. Secondly, the doped ions enter the carbon quantum dot lattice, changing the energy band structure and surface properties. The C==O–NH covalent bonds formed between carbon quantum dots and polymer chains, the hydrogen bonds formed between functional groups, and CQDs 21 The van der Waals force enhances the flexibility of the resin. However, most of the current preparation and doping methods of carbon quantum dots require organic solvents as raw materials, which not only increases the preparation cost, but also poses certain safety hazards. Moreover, the preparation time of carbon quantum dots is long and the yield is low. Therefore, the existing methods need to be further improved and perfected, and it is urgent to develop a low-toxic, safe, and high-yield carbon quantum dot preparation method. However, the technology of doping only with ordinary heteroatoms has been saturated, such as the N, S doping system, and this patent not only has the strengthening ability of the heteroatom itself, but also the addition of metal atoms greatly improves the hardness and conductivity of the water-based epoxy resin. What is different from the previous doping is that the preparation process of doping metal atoms in this patent is simple, low-toxic and safe, and the effect is more obvious.

[0004] This patent uses low-toxic and safe raw materials to prepare self-dispersed nitrogen-copper modified carbon quantum dots waterborne epoxy resin anti-corrosion coatings. Adding self-dispersed nitrogen-copper modified carbon quantum dots to waterborne epoxy resin can effectively enhance the anti-corrosion and impact resistance of the coating. Summary of the invention

[0005] The present invention provides a preparation method and application of a self-dispersed nitrogen copper modified carbon quantum dot waterborne epoxy resin anticorrosion coating, which uses a self-dispersed nitrogen copper modified carbon quantum dot waterborne epoxy resin coating to perform anticorrosion treatment on the surface of a steel sheet, thereby solving the problems of poor conductivity and poor dispersibility of waterborne epoxy resin. In addition, the tensile strength is significantly improved, and the hardness is also significantly improved.

[0006] The present invention aims to enhance the anti-corrosion performance of waterborne epoxy resin by using self-dispersed nitrogen copper modified carbon quantum dots, improve the conductivity of carbon quantum dots, improve their dispersibility in waterborne epoxy resin, and greatly enhance the corrosion resistance of waterborne epoxy resin.

[0007] The technical solution of the present invention is: a method for preparing a self-dispersed nitrogen copper modified carbon quantum dot waterborne epoxy resin anticorrosive coating, characterized in that it comprises: Step 1: Preparation of self-dispersed nitrogen copper modified carbon quantum dots; citric acid, disodium ethylenediaminetetraacetate, and copper nitrate were evenly dispersed in deionized water and anhydrous ethanol by ultrasonic treatment for 5-15 min, stirred for 10 min to make them completely dispersed, and the mixture was poured into a polytetrafluoroethylene reactor, placed in an oven at 180°C for reaction for 10 hours, and heated in a water bath; Step 2: Preparation of self-dispersed nitrogen-copper modified carbon quantum dot powder; centrifuge the nitrogen-copper carbon quantum dot solution prepared in step 1 for 15 min, and filter the supernatant using a 0.22 μm membrane; in order to remove non-reactive molecules, purify the prepared solution using a dialysis bag (molecular weight cutoff 3.0 kDa) for 24 h, replace deionized water every 3 h, and then freeze-dry to obtain black solid nitrogen-copper modified carbon quantum dots N,Cu-CQDs, which are ground into black solid powder using a mortar; Step 3: Preparation of self-dispersed nitrogen-copper modified carbon quantum dot waterborne epoxy resin anti-corrosion coating; add the black solid powder N,Cu-CQDs obtained in step 2 to a certain proportion of mixed waterborne epoxy resin and curing agent, stir well for 20 minutes, and prepare nitrogen-copper modified carbon quantum dot waterborne epoxy resin anti-corrosion coating.

[0008] The above scheme also includes: The synthesis method of nitrogen copper carbon quantum dots in step 1 comprises: Step 1-1: dissolve the carbon source citric acid, the nitrogen source disodium ethylenediaminetetraacetate and the copper source copper nitrate in deionized water and anhydrous ethanol, and stir thoroughly to mix the carbon source, nitrogen source and copper source evenly to obtain a precursor solution.

[0009] Step 1-2: The precursor solution obtained in step 1-1 is transferred into a high-pressure reactor, placed in an oven, and subjected to a hydrothermal reaction under high temperature and high pressure.

[0010] Step 1-3: After the reaction is completed, the hydrothermal product is taken out, centrifuged, filtered, evaporated and concentrated, and dried in sequence, and ground in a mortar to obtain nitrogen-copper-modified carbon quantum dot powder.

[0011] The carbon source citric acid in step 1-1 can be replaced by 4-aminosalicylic acid, the nitrogen source disodium ethylenediaminetetraacetate can be replaced by urea, and the copper source copper nitrate can be replaced by copper sulfate.

[0012] The mass ratio of the carbon source, the nitrogen source and the copper source in step 1-1 is 3:4:1.

[0013] The temperature range of the hydrothermal reaction in step 1-2 is 180-200° C., and the reaction time is about 8-12 h.

[0014] The ultrasonic time is 15 min.

[0015] In step 3, the temperature of the vacuum drying treatment is 70-75°C, and the drying time is 7-8 h; the solvent is deionized water and anhydrous ethanol, and the mass ratio of the added water-based epoxy resin, the curing agent and the nitrogen copper modified carbon quantum dots is 100:85:(0.5~1.5) Preparation of the metal anti-corrosion coating: The self-dispersed nitrogen copper modified carbon quantum dot water-based epoxy resin anti-corrosion coating obtained in step 3 is evenly applied to the surface of Q235 steel, and cured at room temperature for 48 hours to obtain a composite anti-corrosion coating.

[0016] The advantages of the present invention are: 1. The EIS (electrochemical impedance spectroscopy) results show that 1% N,Cu-CQDs / WEP coating has good corrosion resistance to Q235 steel, and the corrosion inhibition rate of the coating on the steel plate reaches 96.9%. SEM (scanning electron microscope) and XPS (X-ray photoelectron spectroscopy) results show that the N,Cu-CQDs / WEP coating is adsorbed on the steel surface to form a stable protective layer, which effectively prevents the interaction between the steel plate and the corrosive elements. 2. The introduction of carbon quantum dots can not only increase the cross-linking density of water-based epoxy resin, but also has the ability to adhere to the surface of the steel plate through metal coordination to form a protective film. Nano-scale CQDs can fill the defects of the coating. 3. Through the impedance spectra of carbon quantum dot-modified epoxy coating and nitrogen-copper-modified carbon quantum dot-modified epoxy resin coating, after fitting, the charge transfer resistance of carbon quantum dot-modified epoxy resin coating and nitrogen-copper-modified carbon quantum dot-modified epoxy resin coating are 1.5×10 5 Ω and 2.1×10 11Ω, indicating that the conductivity of the anti-corrosion coating modified with nitrogen-containing copper-carbon quantum dots is significantly improved, which is beneficial to improving the overall anti-corrosion performance of the coating. 4. Through the scanning electron microscopy images of carbon quantum dot waterborne epoxy resin and the scanning electron microscopy images of nitrogen-copper modified carbon quantum dots modified waterborne epoxy resin, it can be seen that the size of nitrogen-copper modified carbon quantum dots (73.4μm) is smaller than that of pure carbon quantum dots (125.9μm), and the size distribution is more uniform. The nitrogen-copper modified carbon quantum dots have excellent dispersibility in the solvent and do not stratify during high-speed centrifugation.

[0017] The embodiments of the present invention will be described in further detail below with reference to examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a flow chart of the preparation method of the present invention.

[0019] Figure 2 This is a scanning electron microscope image of carbon quantum dot-modified waterborne epoxy resin.

[0020] Figure 3 This is a scanning electron microscope image of nitrogen-copper modified carbon quantum dots modified water-based epoxy resin.

[0021] Figure 4 Curve 1 in the middle is the infrared spectrum of carbon quantum dots, and curve 2 is the infrared spectrum of nitrogen-copper modified carbon quantum dots.

[0022] Figure 5 Curve 3 in the middle is the XRD graph of carbon quantum dots, and curve 4 is the XRD graph of nitrogen-copper modified carbon quantum dots.

[0023] Figure 6 This is a transmission electron micrograph of self-dispersed nitrogen-copper modified carbon quantum dots and its particle size statistics.

[0024] Figure 7 The middle curve is the electrochemical impedance spectrum of Q235 carbon steel coated with nitrogen-containing carbon quantum dot modified epoxy coating after being immersed in 3.5wt% NaCl solution for 14 days.

[0025] Figure 8 The middle curve is the electrochemical impedance spectrum of Q235 carbon steel coated with nitrogen-copper-modified carbon quantum dot epoxy coating and immersed in 3.5wt% NaCl solution for 14 days. DETAILED DESCRIPTION Example 1

[0026] Weigh 3 g of citric acid, 4 g of disodium ethylenediaminetetraacetate, and 1 g of copper nitrate, and dissolve them in a mixture of 100 mL of deionized water and anhydrous ethanol and stir them after ultrasonic treatment for 15 minutes; place the precursor aqueous solution in a hydrothermal reactor, heat it to 180°C, and keep it warm for 8 hours. After the reaction is completed, naturally cool it to room temperature, open the hydrothermal reactor, and obtain a mixture of nitrogen-containing carbon quantum dots, large-particle carbon slag, and precursor pyrolysis products.

[0027] The hydrothermolysis product was added to a 10 mL centrifuge tube and centrifuged at 11000 r / min for 15 min to collect the supernatant. The supernatant was filtered using an aqueous microporous filter membrane with a pore size of 0.22 μm to remove larger particles of carbon residue and free monomers, and the filtrate was collected. The carbon quantum dot aqueous solution was dialyzed in deionized water for 48 h to remove small molecules such as monomers. The dialyzate was concentrated by a rotary evaporator and dried in a vacuum oven (70 ° C) to obtain nitrogen-copper modified carbon quantum dots.

[0028] Q235 carbon steel (carbon content 0.25%-0.45%) with a size of 30mm×60mm×1mm was selected, and the steel sheet was polished with coarse sandpaper until the metallic luster was exposed, and then rinsed with anhydrous ethanol. 0.08g of nitrogen-copper-modified carbon quantum dots was weighed with an electronic scale, added to 8g of water-based epoxy resin, stirred evenly with a weighing spoon, and then 6.8g of epoxy resin curing agent was added to prepare nitrogen-copper-modified carbon quantum dot epoxy resin coating. A plastic scraper was used to evenly apply the prepared nitrogen-copper-modified carbon quantum dot modified water-based epoxy resin coating on the surface of Q235 carbon steel. The steel sheet was placed horizontally for about 48h, and the coating was completely cured. The cured steel sheet was immersed in 3.5wt% NaCl solution for 14 d, and morphological analysis (SEM) and electrochemical (EIS) tests were performed. Example 2

[0029] Weigh 6 g of citric acid, 8 g of disodium ethylenediaminetetraacetate, and 2 g of copper nitrate, perform ultrasonic treatment for 10 min, dissolve in 200 mL of deionized water and stir; place the precursor aqueous solution in a high-pressure reactor, heat to 180 ° C, and keep warm for 8 h. After the reaction is completed, naturally cool to room temperature, open the high-pressure reactor, and obtain a mixed solution of nitrogen-containing carbon quantum dots, large-particle carbon slag, and precursor pyrolysis products.

[0030] The hydrothermal pyrolysis product was placed in a 10 mL centrifuge tube and centrifuged in a 11000 r / min high-speed centrifuge for 15 min. The supernatant was collected and filtered through an aqueous microporous filter membrane with a pore size of 0.22 μm to remove large particles of carbon residue and free monomers, and the filtrate was collected. The nitrogen-containing carbon quantum dot aqueous solution was dialyzed in deionized water for 48 h to remove small molecular substances such as monomers. The dialyzate was concentrated by a rotary evaporator and dried in a vacuum oven (70°C) to obtain nitrogen-containing carbon quantum dots.

[0031] Prepare 3.5wt% NaCl solution for use; select Q235 carbon steel sheet (carbon content 0.25%-0.45%) with a size of 30mm×60mm×1mm, use coarse sandpaper to polish the carbon steel until the bare metal luster is exposed, and rinse with anhydrous ethanol. Use an electronic scale to weigh 0.1g nitrogen copper carbon quantum dots, add it to 8g water-based epoxy resin, and stir it manually with a weighing spoon; add 6.8g epoxy resin curing agent, stir it evenly with a weighing spoon to make nitrogen copper modified carbon quantum dot epoxy coating. Use a plastic scraper to evenly apply the prepared nitrogen copper modified carbon quantum dot modified epoxy coating on the surface of the steel sheet. The steel sheet is placed horizontally for about 10h, and the coating is completely cured. The cured steel sheet was immersed in 3.5wt% NaCl solution for 14 days, and morphological analysis (SEM) and electrochemical (EIS) characterization were performed. Example 3

[0032] Weigh 1.5 g of citric acid, 2 g of disodium ethylenediaminetetraacetate, and 0.5 g of copper nitrate and perform ultrasonic treatment for 5 minutes. Dissolve the three in 50 mL of a mixture of deionized water and anhydrous ethanol and stir. Place the precursor aqueous solution in a hydrothermal reactor, heat to 200°C, and keep warm for 10 hours. After the reaction is completed, naturally cool to room temperature, open the hydrothermal reactor, and obtain a mixture of nitrogen-containing carbon quantum dots, large-particle carbon slag, and precursor pyrolysis products.

[0033] The hydrothermolysis product was added to a 10 mL centrifuge tube and centrifuged at 11000 r / min for 15 min to collect the supernatant. The supernatant was filtered using an aqueous microporous filter membrane with a pore size of 0.22 μm to remove larger particles of carbon residue and free monomers, and the filtrate was collected. The carbon quantum dot aqueous solution was dialyzed in deionized water for 48 h to remove small molecules such as monomers. The dialyzate was concentrated by a rotary evaporator and dried in a vacuum oven (70 ° C) to obtain nitrogen-copper modified carbon quantum dots.

[0034] Q235 carbon steel (carbon content 0.25%-0.45%) with a size of 30mm×60mm×1mm was selected, and the steel sheet was polished with coarse sandpaper until the metallic luster was exposed, and then rinsed with anhydrous ethanol. 0.08g of nitrogen-copper-modified carbon quantum dots was weighed with an electronic scale, added to 8g of water-based epoxy resin, stirred evenly with a weighing spoon, and then 6.8g of epoxy resin curing agent was added to prepare nitrogen-copper-modified carbon quantum dot epoxy resin coating. A plastic scraper was used to evenly apply the prepared nitrogen-copper-modified carbon quantum dot modified water-based epoxy resin coating on the surface of Q235 carbon steel. The steel sheet was placed horizontally for about 48h, and the coating was completely cured. The cured steel sheet was immersed in 3.5wt% NaCl solution for 14 d, and morphological analysis (SEM) and electrochemical test (EIS) were performed. Example 4

[0035] Weigh 6 g of citric acid, 8 g of disodium ethylenediaminetetraacetate, and 2 g of copper nitrate and perform ultrasonic treatment for 15 minutes. Dissolve the three in a mixture of 200 mL of deionized water and anhydrous ethanol and stir. Place the precursor aqueous solution in a hydrothermal reactor, heat to 180°C, and keep warm for 8 hours. After the reaction is completed, naturally cool to room temperature, open the hydrothermal reactor, and obtain a mixture of nitrogen-containing carbon quantum dots, large-particle carbon slag, and precursor pyrolysis products.

[0036] The hydrothermolysis product was added to a 10 mL centrifuge tube and centrifuged at 11000 r / min for 10 min to collect the supernatant. The supernatant was filtered using an aqueous microporous filter membrane with a pore size of 0.22 μm to remove larger particles of carbon residue and free monomers, and the filtrate was collected. The carbon quantum dot aqueous solution was dialyzed in deionized water for 48 h to remove small molecules such as monomers. The dialyzate was concentrated by a rotary evaporator and dried in a vacuum oven (70 ° C) to obtain nitrogen-copper modified carbon quantum dots.

[0037] Q235 carbon steel (carbon content 0.25%-0.45%) with a size of 30mm×60mm×1mm was selected, and the steel sheet was polished with coarse sandpaper until the metallic luster was exposed, and then rinsed with anhydrous ethanol. 0.05g of nitrogen-copper-modified carbon quantum dots was weighed with an electronic scale, added to 8g of water-based epoxy resin, stirred evenly with a weighing spoon, and then 6.8g of epoxy resin curing agent was added to prepare nitrogen-copper-modified carbon quantum dot epoxy resin coating. A plastic scraper was used to evenly apply the prepared nitrogen-copper-modified carbon quantum dot modified water-based epoxy resin coating on the surface of Q235 carbon steel. The steel sheet was placed horizontally for about 48h, and the coating was completely cured. The cured steel sheet was immersed in 3.5wt% NaCl solution for 14 d, and morphological analysis (SEM) and electrochemical test (EIS) were performed. Example 5

[0038] Weigh 1.5 g of citric acid, 2 g of disodium ethylenediaminetetraacetate, and 0.5 g of copper nitrate and ultrasonicate for 5 minutes. Dissolve the three in 50 mL of a mixture of deionized water and anhydrous ethanol and stir. Place the precursor aqueous solution in a hydrothermal reactor, heat to 180°C, and keep warm for 8 hours. After the reaction is completed, naturally cool to room temperature, open the hydrothermal reactor, and obtain a mixture of nitrogen-containing carbon quantum dots, large-particle carbon slag, and precursor pyrolysis products.

[0039] The hydrothermolysis product was added to a 10 mL centrifuge tube and centrifuged at 11000 r / min for 15 min to collect the supernatant. The supernatant was filtered using an aqueous microporous filter membrane with a pore size of 0.22 μm to remove larger particles of carbon residue and free monomers, and the filtrate was collected. The carbon quantum dot aqueous solution was dialyzed in deionized water for 48 h to remove small molecules such as monomers. The dialyzate was concentrated by a rotary evaporator and dried in a vacuum oven (70 ° C) to obtain nitrogen-copper modified carbon quantum dots.

[0040] Q235 carbon steel (carbon content 0.25%-0.45%) with a size of 30mm×60mm×1mm was selected, and the steel sheet was polished with coarse sandpaper until the metallic luster was exposed, and then rinsed with anhydrous ethanol. 0.1g of nitrogen-copper-modified carbon quantum dots was weighed with an electronic scale, added to 8g of water-based epoxy resin, stirred evenly with a weighing spoon, and then 6.8g of epoxy resin curing agent was added to prepare nitrogen-copper-modified carbon quantum dot epoxy resin coating. A plastic scraper was used to evenly apply the prepared nitrogen-copper-modified carbon quantum dot modified water-based epoxy resin coating on the surface of Q235 carbon steel. The steel sheet was placed horizontally for about 48h, and the coating was completely cured. The cured steel sheet was immersed in 3.5wt% NaCl solution for 14 d, and morphological analysis (SEM) and electrochemical test (EIS) were performed. Example 6

[0041] Weigh 1.5 g of citric acid, 2 g of disodium ethylenediaminetetraacetate, and 0.5 g of copper nitrate and perform ultrasonic treatment for 10 minutes. Dissolve the three in a mixed solution of 50 mL of deionized water and anhydrous ethanol and stir. Place the precursor aqueous solution in a hydrothermal reactor, heat to 200°C, and keep warm for 10 hours. After the reaction is completed, naturally cool to room temperature, open the hydrothermal reactor, and obtain a mixed solution of nitrogen-containing carbon quantum dots, large-particle carbon slag, and precursor pyrolysis products.

[0042] The hydrothermolysis product was added to a 10 mL centrifuge tube and centrifuged at 11000 r / min for 15 min to collect the supernatant. The supernatant was filtered using an aqueous microporous filter membrane with a pore size of 0.22 μm to remove larger particles of carbon residue and free monomers, and the filtrate was collected. The carbon quantum dot aqueous solution was dialyzed in deionized water for 48 h to remove small molecules such as monomers. The dialyzate was concentrated by a rotary evaporator and dried in a vacuum oven (70 ° C) to obtain nitrogen-copper modified carbon quantum dots.

[0043] Q235 carbon steel (carbon content 0.25%-0.45%) with a size of 30mm×60mm×1mm was selected, and the steel sheet was polished with coarse sandpaper until the metallic luster was exposed, and then rinsed with anhydrous ethanol. 0.2g of nitrogen-copper-modified carbon quantum dots was weighed with an electronic scale, added to 8g of water-based epoxy resin, stirred evenly with a weighing spoon, and then 6.8g of epoxy resin curing agent was added to prepare nitrogen-copper-modified carbon quantum dot epoxy resin coating. A plastic scraper was used to evenly apply the prepared nitrogen-copper-modified carbon quantum dot modified water-based epoxy resin coating on the surface of Q235 carbon steel. The steel sheet was placed horizontally for about 48h, and the coating was completely cured. The cured steel sheet was immersed in 3.5wt% NaCl solution for 14 d, and morphological analysis (SEM) and electrochemical (EIS) tests were performed. Example 7

[0044] Weigh 3 g of citric acid, 4 g of disodium ethylenediaminetetraacetate, and 1 g of copper nitrate and perform ultrasonic treatment for 10 minutes. Dissolve the three in a mixed solution of 100 mL of deionized water and anhydrous ethanol and stir. Place the precursor aqueous solution in a hydrothermal reactor, heat to 200°C, and keep warm for 12 hours. After the reaction is completed, naturally cool to room temperature, open the hydrothermal reactor, and obtain a mixed solution of nitrogen-containing carbon quantum dots, large-particle carbon slag, and precursor pyrolysis products.

[0045] The hydrothermolysis product was added to a 10 mL centrifuge tube and centrifuged at 11000 r / min for 10 min to collect the supernatant. The supernatant was filtered using an aqueous microporous filter membrane with a pore size of 0.22 μm to remove larger particles of carbon residue and free monomers, and the filtrate was collected. The carbon quantum dot aqueous solution was dialyzed in deionized water for 48 h to remove small molecules such as monomers. The dialyzate was concentrated by a rotary evaporator and dried in a vacuum oven (70 ° C) to obtain nitrogen-copper modified carbon quantum dots.

[0046] Q235 carbon steel (carbon content 0.25%-0.45%) with a size of 30mm×60mm×1mm was selected, and the steel sheet was polished with coarse sandpaper until the metallic luster was exposed, and then rinsed with anhydrous ethanol. 0.1g of nitrogen-copper-modified carbon quantum dots was weighed with an electronic scale, added to 8g of water-based epoxy resin, stirred evenly with a weighing spoon, and then 6.8g of epoxy resin curing agent was added to prepare nitrogen-copper-modified carbon quantum dot epoxy resin coating. A plastic scraper was used to evenly apply the prepared nitrogen-copper-modified carbon quantum dot modified water-based epoxy resin coating on the surface of Q235 carbon steel. The steel sheet was placed horizontally for about 48h, and the coating was completely cured. The cured steel sheet was immersed in 3.5wt% NaCl solution for 14 d, and morphological analysis (SEM) and electrochemical test (EIS) were performed. Example 8

[0047] Weigh 3 g of citric acid, 4 g of disodium ethylenediaminetetraacetate, and 1 g of copper nitrate and perform ultrasonic treatment for 10 minutes. Dissolve the three in a mixed solution of 100 mL of deionized water and anhydrous ethanol and stir. Place the precursor aqueous solution in a hydrothermal reactor, heat to 200°C, and keep warm for 12 hours. After the reaction is completed, naturally cool to room temperature, open the hydrothermal reactor, and obtain a mixed solution of nitrogen-containing carbon quantum dots, large-particle carbon slag, and precursor pyrolysis products.

[0048] The hydrothermolysis product was added to a 10 mL centrifuge tube and centrifuged at 11000 r / min for 20 min to collect the supernatant. The supernatant was filtered using an aqueous microporous filter membrane with a pore size of 0.22 μm to remove larger particles of carbon residue and free monomers, and the filtrate was collected. The carbon quantum dot aqueous solution was dialyzed in deionized water for 72 h to remove small molecules such as monomers. The dialyzate was concentrated by a rotary evaporator and dried in a vacuum oven (70 ° C) to obtain nitrogen-copper modified carbon quantum dots.

[0049] Q235 carbon steel (carbon content 0.25%-0.45%) with a size of 30mm×60mm×1mm was selected, and the steel sheet was polished with coarse sandpaper until the metallic luster was exposed, and then rinsed with anhydrous ethanol. 0.2g of nitrogen-copper-modified carbon quantum dots was weighed with an electronic scale, added to 8g of water-based epoxy resin, stirred evenly with a weighing spoon, and then 6.8g of epoxy resin curing agent was added to prepare nitrogen-copper-modified carbon quantum dot epoxy resin coating. A plastic scraper was used to evenly apply the prepared nitrogen-copper-modified carbon quantum dot modified water-based epoxy resin coating on the surface of Q235 carbon steel. The steel sheet was placed horizontally for about 48h, and the coating was completely cured. The cured steel sheet was immersed in 3.5wt% NaCl solution for 14 d, and morphological analysis (SEM) and electrochemical test (EIS) were performed.

[0050] Figure 1 This is a flow chart of the preparation method of the present invention. It includes: preparation of self-dispersed nitrogen copper modified carbon quantum dots: → citric acid, copper nitrate, deionized water, anhydrous ethanol → ultrasonic dispersion → stirring → moving to a reactor → placing in an oven at 180°C for reaction for 10 hours → 65°, vacuum drying → preparation of self-dispersed nitrogen copper modified carbon quantum dot powder: → dialysis bag, dialysis for 24 hours → freeze drying → grinding → preparation of self-dispersed nitrogen copper modified carbon quantum dot modified waterborne epoxy resin anticorrosion coating: → self-dispersed nitrogen copper modified carbon quantum dot powder N,Cu-CQDs → waterborne epoxy resin → self-dispersed nitrogen copper modified carbon quantum dot waterborne epoxy resin anticorrosion coating.

[0051] Figure 2 This is a scanning electron microscope image of carbon quantum dot waterborne epoxy resin. Figure 3 This is a scanning electron microscope image of nitrogen-copper modified carbon quantum dots modified waterborne epoxy resin. Overall, the size of nitrogen-copper modified carbon quantum dots (73.4μm) is smaller than that of pure carbon quantum dots (125.9μm), and the size distribution is more uniform. The nitrogen-copper modified carbon quantum dots have excellent dispersibility in the solvent and do not stratify during high-speed centrifugation.

[0052] Figure 4 In the figure, curve 1 is the infrared spectrum of carbon quantum dots, and curve 2 is the infrared spectrum of nitrogen-copper modified carbon quantum dots. N,Cu-CDs at 3500 cm −1 The broad vibration band near 3000 cm is attributed to the -OH stretching vibration (much lower than that of N-CQDs). −1 The absorptions at 1650 cm-1 and 1650 cm-2 are attributed to the stretching and bending vibrations of the CH alkyl groups, respectively. −1 The peak at 1400cm is the stretching vibration of C=O, N, -OH, CH and C=O on the surface of Cu-CQDs. -1 and 1250 cm −1The vibrations at 750 cm-1 and 750 cm-2 belong to the stretching vibrations of CN and CO, respectively. Different from N-CQDs, the FTIR spectra of N and Cu-CQDs are in the metal sensitive region (750 cm-1). -1 -850cm −1 ) appeared N−Cu-N, and N and Cu were successfully co-doped in N,Cu-CQDs.

[0053] Figure 5 In the figure, curve 3 is the XRD graph of carbon quantum dots (X-ray diffractometer), and curve 4 is the XRD graph of nitrogen-copper modified carbon quantum dots. The broad peak centered at 2θ=22° in the XRD spectrum indicates that they have an amorphous carbon structure due to the introduction of nitrogen and oxygen, and there is a broad peak belonging to the (002) plane of graphitic carbon. There is a sharp peak at 2θ=44°, indicating that Cu is doped into the carbon quantum dots.

[0054] Figure 6 This is a transmission electron micrograph of self-dispersed nitrogen-copper modified carbon quantum dots and its particle size statistics. The average size of N,Cu-CDs is 4nm, and the size distribution is mainly between 3.5 and 5.55 nm.

[0055] Figure 7 , Figure 8 The impedance spectra of carbon quantum dot modified epoxy coating and nitrogen copper modified carbon quantum dot modified epoxy resin coating are shown in Figure 2. After fitting, the charge transfer resistance of carbon quantum dot modified epoxy resin coating and nitrogen copper modified carbon quantum dot modified epoxy resin coating are 1.5×10 5 Ω and 2.1×10 7 Ω, indicating that the electrical conductivity of the anti-corrosion coating modified with nitrogen-containing copper carbon quantum dots is significantly improved, which is beneficial to improving the overall anti-corrosion performance of the coating.

[0056] The above description is only a specific implementation mode of the present invention, and various examples do not constitute a limitation on the essential content of the present invention.

Claims

1. A method for preparing a self-dispersed nitrogen copper modified carbon quantum dot waterborne epoxy resin anticorrosive coating, characterized in that: include: Step 1: Preparation of self-dispersed nitrogen copper modified carbon quantum dots; citric acid, disodium ethylenediaminetetraacetate, and copper nitrate were evenly dispersed in deionized water and anhydrous ethanol by ultrasonic treatment for 5-15 min, stirred for 10 min to make them completely dispersed, and the mixture was poured into a polytetrafluoroethylene reactor, placed in an oven at 180°C for reaction for 10 hours, and heated in a water bath; Step 2: Preparation of self-dispersed nitrogen-copper modified carbon quantum dot powder; centrifuge the nitrogen-copper carbon quantum dot solution prepared in step 1 for 15 min, and filter the supernatant using a 0.22 μm membrane; in order to remove non-reactive molecules, purify the prepared solution using a dialysis bag (molecular weight cutoff 3.0 kDa) for 24 h, replace deionized water every 3 h, and then freeze-dry to obtain black solid nitrogen-copper modified carbon quantum dots N,Cu-CQDs, which are ground into black solid powder using a mortar; Step 3: Preparation of self-dispersed nitrogen-copper modified carbon quantum dot water-based epoxy resin anti-corrosion coating; add the black solid powder N,Cu-CQDs obtained in step 2 to a certain proportion of mixed water-based epoxy resin and curing agent, stir well for 20 minutes, and prepare nitrogen-copper modified carbon quantum dot water-based epoxy resin anti-corrosion coating.

2. The method for preparing the self-dispersed nitrogen copper modified carbon quantum dot epoxy resin anticorrosive coating according to claim 1, characterized in that: The synthesis method of nitrogen copper carbon quantum dots in step 1 comprises: Step 1-1: dissolving the carbon source citric acid, the nitrogen source disodium ethylenediaminetetraacetate and the copper source copper nitrate in deionized water and anhydrous ethanol, and stirring thoroughly to mix the carbon source, nitrogen source and copper source evenly to obtain a precursor solution; Step 1-2: The precursor solution obtained in step 1-1 is transferred into a high-pressure reactor, placed in an oven, and subjected to a hydrothermal reaction under high temperature and high pressure; Step 1-3: After the reaction is completed, the hydrothermal product is taken out, centrifuged, filtered, evaporated and concentrated, and dried in sequence, and ground in a mortar to obtain nitrogen-copper-modified carbon quantum dot powder.

3. The method for preparing the self-dispersed nitrogen copper modified carbon quantum dot waterborne epoxy resin anticorrosive coating according to claim 2, characterized in that: The carbon source citric acid in step 1-1 can be replaced by 4-aminosalicylic acid, the nitrogen source disodium ethylenediaminetetraacetate can be replaced by urea, and the copper source copper nitrate can be replaced by copper sulfate.

4. The method for preparing the self-dispersed nitrogen copper modified carbon quantum dot epoxy resin anticorrosive coating according to claim 2 or 3, characterized in that: The mass ratio of the carbon source, the nitrogen source and the copper source in step 1-1 is 3:4:

1.

5. The method for preparing the self-dispersed nitrogen copper modified carbon quantum dot epoxy resin anticorrosive coating according to claim 2, characterized in that: The temperature range of the hydrothermal reaction in step 1-2 is 180-200° C., and the reaction time is about 8-12 h.

6. The method for preparing the self-dispersed nitrogen copper modified carbon quantum dot epoxy resin anticorrosive coating according to claim 1, characterized in that: The ultrasonic time was 15 min.

7. The method for preparing the self-dispersed nitrogen copper modified carbon quantum dot epoxy resin anticorrosive coating according to claim 1, characterized in that: In the step 3, the temperature of the vacuum drying treatment is 70-75° C., and the drying time is 7-8 h; the solvent is deionized water and anhydrous ethanol, and the mass ratio of the added water-based epoxy resin, curing agent and nitrogen-copper modified carbon quantum dots is 100:85:(0.5~1.5).

8. The method for preparing the self-dispersed nitrogen copper modified carbon quantum dot epoxy resin anticorrosive coating according to claim 1, characterized in that: Preparation of metal anti-corrosion coating; the self-dispersed nitrogen copper modified carbon quantum dot water-based epoxy resin anti-corrosion coating obtained in step 3 is evenly applied to the surface of Q235 steel and cured at room temperature for 48 hours to obtain a composite anti-corrosion coating.

Citation Information

Patent Citations

  • Nitrogen and sulfur doped carbon quantum dot modified epoxy resin coating as well as preparation method and application thereof

    CN116333556A

  • Waterborne epoxy composite coating of carbon nanodot modified mica powder and preparation method of waterborne epoxy composite coating

    CN117165147A